ANALISIS QUALITY OF SERVICE JARINGAN VIRTUAL PRIVATE NETWORK (VPN) DI STMIK STIKOM INDONESIA - I Kadek Susila Satwika (JURNAL ILMIAH INFORMATIKA, 2019)
The need to access data remotely is a person's need to be more efficient in doing a job. Currently there are many remote access application programs, one of which is TeamViewer by utilizing the internet public network. By installing a TeamViewer program on a client and server computer someone can do data work and repair remotely as long as it is connected to the internet. To be able to do remote access, of course, a client must already know the user and password from the server computer. The disadvantage of TeamViewer is that other people will easily remote access data simply by entering the user and password that the computer has on the server. To overcome this problem, VPN technology is used with the PPTP protocol where only the IP address of the client that has been registered on the proxy device can access data on the server. VPN allows clients to connect to the server privately through public networks. To find out the performance of the VPN network that is built, QoS (Quality of Service) parameter analysis is needed which includes delay, jitter, throughput and packet loss. From the results of the tests carried out, the results of QOS with an index of 3.75, which if converted to the standard TIPHON, VPN network at STMIK STIKOM Indonesia has a satisfactory quality.